Examination of feral pigeon populations at animal breeding farms - Varga, Sándor; Juhász, Lajos (Acta Agraria Debreceniensis, 2007)
In the course of our examination, we assessed biometric data that determine gender, we evaluated sexual activity, measured the nourishment and necropsies of two feral pigeon populations feeding and nesting at animal breeding farms. The changes in the body weight of the different genders were significant on both farms (p